Semi-syntheses of annotine derivatives and their acetylcholinesterase inhibitory activity in vitro - Borghildur Eiríksdóttir 1985- (2013)
Yfirlýsing barst safninu í lok apríl 2014 undirrituð af einum leiðbeinanda en ekki höfundi. Lycopodium annotinum is a club moss that grows wild in Iceland, it contains various Lycopodium alkaloids. Some Lycopodium alkaloids have found to possess potent acetylcholinesterase (AChE) inhibition and could therefore be used in the treatment of Alzheimer’s disease (AD), for example Huperzine A (HupA). HupA is of lycodine type alkaloid, however in the Lycopodium annotinum lycopodine type alkaloids are in majority. Annotine, one of the lycopodine type alkaloid found in the Lycopodium annotinum, has been tested for AChE activity and showed very weak inhibition (IC50 860 μM). The aim of this research was to semi-synthesize annotine derivatives designed with molecular modeling, determine their structure with NMR spectroscopy and to test the AChE activity on them in vitro, using the Ellman method, in hope of more active derivatives. Annotine was isolated from Lycopodium annotinum and was used as substrate in the semi-synthesis of annotinol which was then used for the semi-syntheses of three derivatives. Their structure was determined with NMR, benzoyl annotine, ortho-fluorobenzoyl annotine and para-fluorobenzoyl annotine. Derivatives were tested for AChE inhibitory activity, but due to poor solubility the para-fluorobenzoyl derivative could not be tested. The activity for the derivatives was greater than for annotine, 145 μM for benzoyl annotine and 248 μM for ortho-fluorobenzoyl annotine. The structure activity relationship (SAR) for the annotine derivatives synthesizes in this research is a good addition to previous knowledge on SAR for lycopodine type derivatives and motivate further in silico research on lycopodine type derivatives which could be more potent inhibitors of the AChE enzyme.